Comparative Study of Genotoxicity of Silver and Gold Nanoparticles Prepared by the Electric Spark Dispersion Method; Journal of Applied Pharmaceutical Science; Vol. 7 (7) - Plotnikov E. V. Evgeny Vladimirovich; Zhuravkov S. P. Sergey Petrovich; Gapeyev A. B. Andrew; Plotnikov V. M. Vladimir Mikhaylovich; Martemjyanova I. V. Irina Vladimirovna; Martemyanov D. V. Dmitry Vladimirovich (2017, 2017)
Title screen